A Systematic Review on Carbon Dioxide (CO2) Emission Measurement Methods under PRISMA Guidelines: Transportation Sustainability and Development Programs - Zubair, Muhammad; Chen, Shuyan; Ma, Yongfeng; Hu, Xiaojian (Sustainability, 2023)
In the effort to urgently develop new and improved methodologies to compute and assess CO2 emissions from transportation, results have been less than ideal; this article provides a review of the methodologies currently available. When it comes to the discharge of harmful gases into the air, transportation is the biggest offender. Methods are still being developed to calculate and analyze the transportation sector’s carbon footprint, despite the fact that the need to limit the emission of gases that contribute to global warming has now become urgent. Previous studies have calculated the carbon footprint of transportation; however, there are some discrepancies in the terminology and methodologies utilized. The commonalities between CO2 emission measurement techniques and assessment techniques are the primary subject of this review. This study helps to increase public awareness of environmental concerns and promotes the use of reliable methodologies for calculating transportation-related CO2 emissions. It is hoped that choosing the optimal available method will contribute to a decrease in CO2 emissions from transportation.